Upaya Peningkatan Minat Calon Siswa melalui Publikasi Program Sekolah Alam CEFA - Adinta Alfita; Emilda Pirdaus; Indi Rahmat Saputra; Sahrul Amanda; Rika Fitri Ramadhani (Penerbit Yayasan Daarul Huda Kruengmane, 2026)
This study examines the promotional and educational outreach activities conducted at Sekolah Alam CEFA, an institution that integrates outdoor project-based learning with intensive character education through its boarding program. The school faces the need to attract new students for the upcoming academic year, increase public interest in campus visits, and disseminate information regarding its facilities, curriculum, and residential programs. Activities carried out by students during the program include observing the learning environment, participating in outdoor academic sessions, and documenting various aspects of the institution’s educational model. The findings indicate that Sekolah Alam CEFA actively seeks to expand public visibility by strengthening community engagement and enhancing promotional strategies. This article presents an overview of the school’s learning approach, the challenges related to student recruitment, and efforts to improve public awareness through direct introduction and publication initiatives.